Media Pembelajaran Berbicara Bahasa Indonesia Kelas Tinggi - Juni Sahla Nasution; Erina Damayanti; Nepri Handayani; Rabiatul Adawiyah Batubara (Protasis: Jurnal Bahasa, Sastra, Budaya, dan Pengajarannya, 2024)
Language has a very important role in human life as a means of daily communication, especially in speaking. Speaking is a way for someone to convey their meaning to another person using words, so that they can be understood. This skill is very crucial, especially for children in elementary school. However, many elementary school students still have difficulty speaking or conveying their ideas and opinions. To overcome this, it is necessary to use learning media that can help develop students' speaking skills. This research uses a qualitative descriptive approach and a type of library research, which collects data from related scientific papers. The results of the literature study show that the use of flash cards as a learning medium can be effective in improving students' speaking skills at the elementary school level. Flash cards contain text, vocabulary, or symbols that help students convey information orally more easily and clearly.